Parlamentskii chas . Parlamentskii chas . Parliamentary Hour . Парламентский час - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Foreign press opinions of Boris Yeltsin; conflict between the Russian President and the Supreme Soviet; Russia's relations with Belarus. Featured in the program: Khasbulatov, Ruslan Imranovich (Chairman of the Supreme Soviet of the Russian Federation); Novikov, Vladimir Il'ich (Chairman of the Council of Deputy Factions); Morokin, Vladimir Ivanovich (Member of the Supreme Council of the Russian Federation); Lukashenko, Aleksandr Grigor'evich (People's Deputy of Belarus) Contributors: Berdnikova, Nina (Anchor) Series description: A program about the activity of the Supreme Soviet of the Russian Federation. Высказывания о Борисе Ельцине в зарубежная прессе России; конфликт между Президентом России и Верховным Советом; проблема отношений России с Беларусью. В программе участвуют: Хасбулатов, Руслан Имранович (Председатель Верховного Совета Российской Федерации); Новиков, Владимир Ильич (Председатель Совета депутатских фракций); Морокин, Владимир Иванович (Член Верховного совета Российской Федерации); Лукашенко, Александр Григорьевич (Народный депутат Беларуси) Создатели: Бердникова, Нина (Ведущий/Ведущая) Описание серии: Передача о деятельности Верховного Совета Российской Федерации.